Effect of initial blank temperature in hot press forming towards 22MnB5 springback failure - C. H., Ng; C. F., Lai; S. N. M., Yahaya; S., Shamsudin; S. N., Aqida; F., Sharrifuddin (Faculty Mechanical Engineering, UMP, 2019)
The springback failure of ultra-high strength boron steel (22MnB5) in hot press forming (HPF) process was characterized under bending and membrane conditions. Hot press forming for U–shaped parts with ultra-high strength boron steel were experimented and simulated to study the effect of initial blank temperatures on springback failure in the automotive industry. The results specify the various preheated temperature of 22MnB5 blank effect toward springback occurrences with reference to hot press forming dies design. ANSYS Workbench was used to verify finite element (FE) simulations of the processes in order to consolidate the knowledge of springback. The validated numerical simulation model were used in analyzing the stress and strain distributions along the formed part in the FE models, it was found that the springback angle was related in averaging value throughout quenching, regardless of the forming conditions. Springback failure mainly caused dimension deviation in hot press form parts due to the impact of thermal restoring moments and quenching rate of hot press forming process.